Neurovegetative Criteria for Evaluation of Cerebral Circulation Recovery of the Resuscitated Organism - A. Ya. Yevtushenko; A. V. Budayev; A. I. Etenko; A. S. Razumov (Общая реаниматология, 2009)
Objective: to assess the diagnostic informative value of some neurovegetative parameters as criteria for evaluating the adequacy of cerebral circulatory recovery at the early stage of resuscitation. Materials and methods. Experiments were performed on 65 cats under anesthesia with nembutal, 45 mg/kg intraperitoneally. A model of 5-minute clinical death from prolonged blood loss (50 mm Hg, a Wiggers hemobarostat) was employed. Cerebral circulation (hydrogen clearance), cardiac output, and its distribution (thermodilution) were recorded. The autonomic indices, such as the Kerdo, Algover, Robinson, and Hilebrant ones, were calculated. An index of regulatory system tension was estimated (analysis of cardiac rhythm variability). Results. There was a close, direct correlation of postresuscitative changes in cerebral circulation with cardiac output and its redistribution. The phasic pattern of cerebral circulatory recovery is reflected by the time course of changes in the neurovegetative indices. In hyperperfusion, the baseline levels of the Kerdo and Algover indices were associated with the low values of the Robinson and Hilebrant indices and tension index. Conclusion. The neurovegetative parameters are of the most informative value in inadequate brain perfusion (considerable increases in the Kerdo and Algover indices and a reduction in the Robinson index). In brain blood overperfusion that is beyond the adaptive ranges, these parameters (apart from the tension index) do not change as those in the surviving animals. The practical use of the indices requires additional experimental and clinical studies. Key words: postresuscitative period, cerebral circulation, cardiac output distribution, neurovegetative indices.